Factors Influencing Teacher Behavior with Students with Diverse Learning and Behavioral Needs - Schultz, Edward K.; Simpson, Cynthia G. (Journal of the American Academy of Special Education Professionals, 2013)
Over the last two decades, inclusion has become a critical part of the reform efforts to improve the delivery of services to students with disabilities. As general education teachers are asked to assume greater responsibility for students with diverse learning and behavior needs, it is important to examine factors that influence their teaching behavior while instructing students identified at risk or with specific learning disabilities. Factors influencing teacher behavior with students who have diverse learning and behavioral needs being served in inclusive environments are addressed, including: (a) teacher expectations of student behavior, (b) attribution patterns, (c) teacher attitudes toward inclusion, (d) personal teacher efficacy, and (e) teacher qualities.